Role of cardiotrophin‐1 in the regulation of metabolic circadian rhythms and adipose core clock genes in mice and characterization of 24‐h circulating CT‐1 profiles in normal‐weight and overweight/obese subjects. Issue 4 (17th January 2017) - Lópeź‐Yoldi, Miguel; Stanhope, Kimber L.; Garaulet, Marta; Chen, X. Guoxia; Marcos‐Gómeź, Beatriz; Carrasco‐Benso, María Paz; Maria, Eva M. Santa; Escoté, Xavier; Lee, Vivien; Nunez, Marinelle V.; Medici, Valentina; Martínez‐Ansó, Eduardo; et al.
Abstract : Cardiotrophin (CT)‐1 is a regulator of glucose and lipid homeostasis. In the present study, we analyzed whether CT‐1 also acts to peripherally regulate metabolic rhythms and adipose tissue core clock genes in mice. Moreover, the circadian pattern of plasma CT‐1 levels was evaluated in normal‐weight and overweight subjects. The circadian rhythmicity of oxygen consumption rate (VO2 ) was disrupted in aged obese CT‐1‐deficient (CT‐1 −/− ) mice (12 mo). Although circadian rhythms of VO2 were conserved in young lean CT‐1 −/− mice (2 mo), CT‐1 deficiency caused a phase shift of the acrophase. Most of the clock genes studied ( Clock, Bmal1, and Per2 ) displayed a circadian rhythm in adipose tissue of both wild‐type (WT) and CT‐1 −/− mice. However, the pattern was altered in CT‐1 −/− mice toward a lower percentage of the rhythm or lower amplitude, especially for Bmal1 and Clock . Moreover, CT‐1 mRNA levels in adipose tissue showed significant circadian fluctuations in young WT mice. In humans, CT‐1 plasma profile exhibited a 24‐h circadian rhythm in normal‐weight but not in overweight subjects. The 24‐h pattern of CT‐1 was characterized by a pronounced increase during the night (from 02:00 to 08:00). These observations suggest a potential role for CT‐1 in the regulation of metabolic circadian rhythms. —Lópeź‐Yoldi, M., Stanhope, K. L., Garaulet, M., Chen, X. G., Marcos‐Gómeź, B., Carrasco‐Benso, M. P., Sánta Maria, E. M., Escoté, X., Lee, V., Nunez, M. V., Medici, V., Martínez‐Ansó, E., Sainź, N., Huerta, A. E., Laiglesia, L. M., Prieto, J., Martínez, J. A., Bustos, M., Havel, P. J., Moreno‐Aliaga, M. J. Role of cardiotrophin‐1 in the regulation of metabolic circadian rhythms and adipose core clock genes in mice and characterization of 24‐h circulating CT‐1 profiles in normal‐weight and overweight/obese subjects. FASEB J . 31, 1639–1649 (2017) www.fasebj.org